Signal filtration in a piezoelectric-semiconductor convolver with broad-band transducers - KAWALEC, A. M. (Archives of Acoustics, 1994)
The result of theoretical and experimental studies of a convolver in piezoelectric-semiconductor configuration (BGO-Si) are presented. Experimental results with using of the convolver for compression a signal with linear frequency modulation have been reported. Dispersive excitation transducers were used to improve the matching of the convolver inputs to the external sources of the signals in the pass band. A new measurement system for the amplitude characteristics of the convolver output has been proposed.